Initiatives for rural development through collective action: the case of household participation in group activities in the highlands of Central Kenya - Kariuki, Gatarwa; Place, Frank (International Food Policy Research Institute, 2005)
Dimensions of the nature, scope, and complexity of collective action in Kenya have evolved over many years. In studying collective action, the aim is to understand why and how people participate in networks of trust. The purpose of this study was to investigate the different objectives that farmers pursue through collective action with the aim of understanding the patterns of people’s participation in collective action, identify factors that influence people to join groups, and identify the costs and benefits of participating in activities of groups. The study was carried out in four sites spread across the highlands of central Kenya. Data was collected from a total of 442 households, focusing on whether members of those households belonged to groups and if so, what type of groups these were and their activities. In addition we looked at how these groups functioned and identified some of the contributions members make to these groups and the benefits from the same. The analysis shows that collective action is used to accomplish a range of activities for different socioeconomic categories and that the majority of households in central Kenya engage in some form of group activity.... The study suggests that where institutions and policies that promote individual or private sector growth are weak, collective action can help to overcome these weaknesses and connect individuals in these institutions and policies.